Impact of size of banks and insurance companies on their profitability in Bosnia and Herzegovina (The Journal of Forensic Accounting Profession, 2024)
In this paper, we investigate the determinants of bank profitability by examining endogenous factors used to measure the size of a financial institution. We underscore the significance of bank employees in embodying institutional values and playing a pivotal role in sales channels, as well as the impact of technological integration on customer expectations and workforce dynamics. Utilizing a dataset from regulatory agencies, which includes information from 47 banks and insurance companies in Bosnia and Herzegovina for the year 2021, the study explores the relationship between the independent variables which include the volume of total assets and the number of employees, and the dependent variable for profitability. By calculating Return on Equity (ROE) and employing a multiple linear regression model, the study finds that a statistically significant relation between independent variables and the dependent variable does not exist. Despite this, the research highlights the need for further investigation, particularly considering the differentiation between banks and insurance companies, the potential impact of outliers, and the broader economic context of the year studied. The findings suggest that a more refined model, possibly incorporating panel data, could provide clearer insights into the profitability determinants of financial institutions in Bosnia and Herzegovina.(Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2024-0003, pod licencom CC BY-NC-ND 4.0)
Keywords: financial institutions; profitability; employees; Bosnia and Herzegovina